Blepharocele following Head Injury in a Child - Bhatoe, Harjinder Singh (Indian Journal of Neurotrauma, 2005)
Periorbital swelling is a common accompaniment of head injury. However, blepharocele is a rare complication of skull base injury involving the orbital roof. We present one 2-year-old child who developed blepharocele due to orbital rim fracture and basal dural tear. Her vision had remained intact. The lesion resolved completely after surgical repair of the basal dura.
Keywords: blepharocele; eye injury; head injury; skull base fracture; ocular encephalocele